Tracking the effects of dyslexia in reading and spelling development: A longitudinal study of Greek readers. (5th January 2018) - Diamanti, Vassiliki; Goulandris, Nata; Stuart, Morag; Campbell, Ruth; Protopapas, Athanassios
Abstract : In this study, we followed Greek children with and without dyslexia for 18 months, assessing them twice on a battery of phonological, reading, and spelling tasks, aiming to document the relative progress achieved and to uncover any specific effects of dyslexia in the development of reading and spelling beyond the longitudinal associations among variables that are observed in typical readers. A wide‐ranging match was achieved between the dyslexic group and the younger reading‐matched comparison group, enabling longitudinal comparisons on essentially identical initial performance profiles. Group differences were found in the development of tasks relying on phonological processing skill, such as phoneme deletion in pseudowords, pseudoword reading accuracy and time, as well as in graphemic spelling accuracy. The results confirm findings from cross‐sectional studies of reading difficulty in the relatively transparent Greek orthography and are consistent with a phonological processing deficit underlying and reciprocally interacting with underdevelopment of reading and spelling skills in the impaired population.